A Structured and Unstructured grid Relocatable ocean platform for Forecasting (SURF). (November 2016) - Trotta, Francesco; Fenu, Elisa; Pinardi, Nadia; Bruciaferri, Diego; Giacomelli, Luca; Federico, Ivan; Coppini, Giovanni
Abstract: We present a numerical platform named Structured and Unstructured grid Relocatable ocean platform for Forecasting (SURF). The platform is developed for short-time forecasts and is designed to be embedded in any region of the large-scale Mediterranean Forecasting System (MFS) via downscaling. We employ CTD data collected during a campaign around the Elba island to calibrate and validate SURF. The model requires an initial spin up period of a few days in order to adapt the initial interpolated fields and the subsequent solutions to the higher-resolution nested grids adopted by SURF. Through a comparison with the CTD data, we quantify the improvement obtained by SURF model compared to the coarse-resolution MFS model.